Protein Microarrays for Quantitative Detection of PAI-1 in Serum - Ma, Xu; Zhang, Qing-yun (Chinese Journal of Cancer Research; Vol 24, No 3 (September 01, 2012): Chinese Journal of Cancer Research, 2012)
Objective: Plasminogen activator inhibitor-1 (PAI-1), one crucial component of the plasminogen activator system, is a major player in the pathogenesis of many vascular diseases as well as in cancer. High levels of PAI-1 in breast cancer tissue are associated with poor prognosis. The aim of this study is to evaluate rigorously the potential of serum PAI-1 concentration functioning as a general screening test in diagnostic or prognostic assays. Methods: A protein-microarray-based sandwich fluorescence immunoassay (FIA) was developed to detect PAI-1 in serum. Several conditions of this microarray-based FIA were optimized to establish an efficacious method. Serum specimens of 84 healthy women and 285 women with breast cancer were analyzed using the optimized FIA microarray. Results: The median serum PAI-1 level of breast cancer patients was higher than that of healthy women (109.7 ng/ml vs. 63.4 ng/ml). Analysis of covariance revealed that PAI-1 levels of the two groups were significantly different (P